The relationship of gastroesophageal reflux disease and asthma control - Arzoe Singh; Rahul Khanna; Annya Suman; Jack Pollack; Sudhir Sekhsaria (European Clinical Respiratory Journal)
Purpose To study whether ACT responses are confounded by gastro-esophageal status (GERD), and if this is in concordance with the variation in Forced Expiratory Volume in 1 second (FEV1%) and Fractional Excretion of Nitric Oxide (FeNO).Materials and Methods This is a prospective cohort study (n = 307). Patients were surveyed for demographics data, and underwent ACT scoring, FEV1% and FeNO testing.Results Patients with GERD had mean ACT scores that were 4.1 (p < .001) lower than without-GERD group. Not-well-controlled asthmatics (FEV1% <80, high FeNO) with-GERD had mean ACT scores that were 2.9 (p < .001) for FEV1% <80 and 3.8 (p = .008) for high FeNO lower than without-GERD group respectively. Well-controlled asthmatics (FEV1% ≥80, low FeNO) with-GERD had mean ACT scores that were 5.2 (p < .001) for FEV1% ≥80 and 5.1 (p < .001) for low FeNO lower than without-GERD group respectively.Conclusion Our study demonstrates that symptoms of GERD can lead to an inaccurate perception of asthma control and ACT as compared to objective measures, such as FEV1% and FeNO. Hence, this can lead to mismanagement of asthma, especially when objective measures are not conducted along with ACT.